The Influence of Parenting Styles on Students' Learning Interest at MA Al-Huda, Gorontalo City, 2025/2026 Academic Year - Elvia Safia; Kamto Kamto (MASI Mandiri Edukasi, 2026)
The significance of learning interest as a prerequisite for academic success serves as the driving force behind this study. However, there are currently few studies that explicitly examine the relationship between parenting styles and learning interests in the context of madrasahs, particularly in Islamic Religious Education courses. Thus, for the academic year 2025–2026, this study intends to examine the connection between parenting practices and students' enthusiasm in learning at MA Al-Huda Kota Gorontalo. This study employs an ex post facto correlational design and a quantitative methodology. A random selection procedure was used to select 112 respondents from the 156 students who comprised the research population. A Likert-scale questionnaire that had undergone validity and reliability testing was used to collect the data, and Pearson correlation and simple linear regression were used for analysis. The study's findings show that parenting style and students' motivation in learning are positively and statistically significantly correlated, albeit the correlation is weak (r = 0.232). Parenting style's 5.4% contribution to learning interest is likewise regarded as modest, suggesting that the majority of learning interest is impacted by variables not included in this study. In addition to enhancing research in the setting of madrasahs and Islamic Religious Education, this study makes theoretical advances by claiming that parenting style is a contextual factor related to learning interest but not a dominant factor. Practically speaking, the study's findings highlight how crucial it is for family parenting practices and the educational setting to work together to boost students' enthusiasm for learning